Transforming Education in Indonesia Through Digital Schools at Smpn 15 Mataram - Chelyna Ikhtiar; Amryna Febriani; Mohammad Mustari (Penerbit Hellow Pustaka, 2025)
The rapid advancement of digital technology has brought significant changes to the field of education, including in Indonesia. The ongoing transformation of education aims to create a more interactive, efficient, and relevant learning system that aligns with the demands of the modern era. SMPN 15 Mataram has emerged as one of the schools pioneering the implementation of a digital school concept as a concrete step toward educational modernization. This study aims to describe the process of educational transformation through the adoption of digital school practices at SMPN 15 Mataram and to analyze their impact on the teaching and learning process. The research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The findings reveal that the integration of digital systems—such as online learning platforms, interactive media, and technology-based administration—has enhanced learning effectiveness and increased student engagement in classroom activities. Nevertheless, several challenges remain, including limited infrastructure and varying levels of digital literacy that require continuous improvement. This transformation is expected to serve as a sustainable model of educational innovation in the digital era.